Probing the magnetic ground state of single crystalline Ce3TiSb5. (27th February 2017) - Matin, M; Kulkarni, R; Thamizhavel, A; Dhar, S K; Provino, A; Manfrinetti, P
Abstract: Motivated by the report of superconductivity in R3 TiSb5 (R  =  La and Ce) and possibly Nd3 TiSb5 at  ̃4 K, we grew single crystals of La3 TiSb5 and Ce3 TiSb5 by the high-temperature solution method using Sn as a flux. While in both compounds we observed a superconducting transition at 3.7 K for resistivity and low-field magnetization, our data conclusively show that it arose from residual Sn flux present in the single crystals. In particular, the heat capacity data do not present any of the anomalies expected from a bulk superconducting transition. The anisotropic magnetic properties of Ce3 TiSb5, crystallizing in a hexagonal P 63 / mcm structure, were studied in detail. We find that the Ce ions in Ce3 TiSb5 form a Kondo lattice and exhibited antiferromagnetic ordering at 5.5 K with a reduced moment and a moderately normalized Sommerfeld coefficient of 598 mJ/mol K 2 . The characteristic single-ion Kondo energy scale was found to be  ̃8 K. The magnetization data were subjected to a crystal electric field (CEF) analysis. The experimentally observed Schottky peak in the 4 f -electron heat capacity of Ce3 TiSb5 was reproduced fairly well by the energy levels derived from the CEF analysis.